Data sources on migrants' labour market and education integration in Austria - Peter Huber; Marian Fink; Gerard Thomas Horvath (Austrian Institute of Economic Research (WIFO), 2020)
As part of a larger research project, we survey existing data sets and research results on immigrants' integration success in Austria focusing on educational and labour market outcomes. We consider different registers as well as survey data available to researchers on a regular basis and compare to what extent these data contain relevant information on immigrants and their educational and employment careers and survey the research that has been conducted based on the different datasets. We also aim to identify research gaps and potential data gaps resulting from the fragmentation of relevant information over different data sets. While different data sources contain different aspects relevant for integration research, a "complete" picture of integration processes as well as the identification of supporting and hindering factors for successful integration typically requires a combination of different data sets that may also enrich longitudinal (register-based) individual data by more detailed characteristics from survey data.
Keywords: J11; C53; F22; O15; R23; J15; H55; I24; 330; dynamic microsimulation; migration; labour market integration; immigrant integration; social security; education